2010
DOI: 10.1002/hep.23758
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Utility of Chromosome 17 and p16 Abnormalities in Fluorescence in Situ Hybridization Tests in Primary Sclerosing Cholangitis

Abstract: We read with great interest the article by Azzalini et al., 1 who demonstrated that cigarette smoking worsens the severity of nonalcoholic fatty liver disease (NAFLD) in obese Zucker rats. In a related letter, Xu and coworkers 2 showed that cigarette smoking may act as a cofactor but not as an independent factor for NAFLD in humans. However, currently it is uncertain whether there is a significant association between smoking patterns and the severity of liver histology among patients with NAFLD. Clarification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Our cohort contained relatively few PSC patients, making significant analysis difficult. Prior studies focused on this population have shown FISH abnormalities detected in patients with pre-malignancy or inflammation harboring these aneuploidies [16,17].…”
Section: Discussionmentioning
confidence: 97%
“…Our cohort contained relatively few PSC patients, making significant analysis difficult. Prior studies focused on this population have shown FISH abnormalities detected in patients with pre-malignancy or inflammation harboring these aneuploidies [16,17].…”
Section: Discussionmentioning
confidence: 97%